PERANCANGAN IDENTITAS DAN MEDIA PROMOSI YAYASAN DHARMA BHAKTI MUSLIM INDONESIA - Ayyub Hamdanu Budi Nurmana; Mut Hanan Naufal (Pusat Riset dan Inovasi Nasional, 2024)
The Dharma Bhakti Muslim Indonesia Foundation is a foundation that runs in social and religious fields. When researched, YDBMI did not yet have an identity and promotional media to support the promotion of the Foundation. Therefore, Researcher wants to introduce YDBMI to the community. Researchers do promotional media design approach to introduce YDBMI to society, because promotional media is considered mass media the effects can be felt immediately. Promotional media used by researchers include: foundation identity. The selection of promotional media refers to STP analysis. Researchers hope that alternative solutions designed by researchers can make YDBMI more advanced and developed.